2018
DOI: 10.1107/s1600576718002807
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure evolution of BaBrCl and BaBrCl:5%Eu up to 1073 K by neutron diffraction

Abstract: BaBrCl:Eu is a promising scintillator material; however, the crystal growth yield must be improved for it to become commercially viable. This study measures strain accumulations in the crystal lattice which can contribute to cracking during post-growth cooling. Neutron diffraction is used to measure the crystal structure of undoped and 5 mol% europium-doped BaBrCl from 303 to 1073 K, approaching the melting point. Rietveld analysis of these data provides the temperature dependence of the thermal and chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Understanding the crystal structure and how it evolves from the melting point down to room temperature is useful for confronting challenges during bulk crystal growth. Single crystals may crack during post-growth cooling, due to phase transitions, anisotropic thermal expansion or lattice strain from the introduction of dopants (Doty et al, 2007;Onken et al, 2018). For elpasolites in particular, structural transitions involving the tilting or distortion of the LiX 6 and MX 6 octahedra have been observed (Flerov et al, 1998), and some of these transitions have been associated with twinning ISSN 1600-5767 (Bezbtosikov et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the crystal structure and how it evolves from the melting point down to room temperature is useful for confronting challenges during bulk crystal growth. Single crystals may crack during post-growth cooling, due to phase transitions, anisotropic thermal expansion or lattice strain from the introduction of dopants (Doty et al, 2007;Onken et al, 2018). For elpasolites in particular, structural transitions involving the tilting or distortion of the LiX 6 and MX 6 octahedra have been observed (Flerov et al, 1998), and some of these transitions have been associated with twinning ISSN 1600-5767 (Bezbtosikov et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…where σ ij are components of the stress tensor, ij are components of the strain tensor, α is the chemical expansion coefficient, and C(r, z) is the europium dopant concentration distribution that arises from segregation during growth. We note that Onken et al [42] reported anisotropic Eu doping strain along different BaBrCl lattice directions; however, we have employed an averaged, isotropic chemical expansion coefficient, α, to simply our analysis. The coefficients E ij correspond to the fundamental elastic constants of an orthorhombic crystal whose c-axis is aligned with the z-axis of a Cartesian coordinate system [11], with indices {1, 2, 3} corresponding to {x, y, z}.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Their results indicated a strong correlation between Eu distribution and cracking and that cracks originated from clusters where Eu concentration gradients were large. Later, Onken et al [42] used neutron diffraction to measure the lattice structure of undoped and 5% Eu-doped BaBrCl crystals at elevated temperatures. They reported anisotropic thermal expansion that produces thermal strain and found significant chemical strain caused by the presence of europium dopant atoms substituting at the barium site.…”
Section: Introductionmentioning
confidence: 99%
“…To yield reliable absolute lattice parameters, the DIFC instrument calibration parameters were fitted for the room-temperature data using the lattice parameters from SC-XRD and were kept constant for the rest of the ND data at higher temperatures. For more details on the data collection and refinement of these neutron diffraction data, see Onken et al (2018).…”
Section: Refinementmentioning
confidence: 99%